Getting wired for growth. - Maree, Karin (MEED: Middle East Economic Digest, 2007)
The article reports on the efforts of Egypt to position itself as the leading outsourcing and software development centre in Middle East with the development of the Smart Village technology park. The park will be home to up to 36,000 employees, and it aims to attract local and global telecommunication and information technology companies. The Egyptian government has been very forthcoming in terms of creating initiatives to provide access to technology in a cheaper way. It has also set up more than 1,500 Internet clubs for lower-income Egyptians.